Depth-dependent mosaic tilt and twist in GaN epilayer： An approximate evaluation - 张金风 聂玉虎 周勇波 田坤 哈微 肖明 张进成 郝跃 (Chinese physics B, 2014)
An approach based on depth-sensitive skew-angle x-ray diffraction （SAXRD） is presented for approximately evalu- ating the depth-dependent mosaic tilt and twist in wurtzite c-plane GaN epilayers. It is found that （103） plane and （101） plane, among the lattice planes not perpendicular to the sample surface, are the best choices to measure the depth profiles of tilt and twist for a GaN epilayer with a thickness of less than 2 μm according to the diffraction geometry of SAXRD. As an illustration, the depth-sensitive （103）/（101） ω-scans of a 1.4-μm GaN film grown by metal-organic chemical vapor deposition on sapphire substrate are measured and analyzed to show the feasibility of this approach.